Expressed Breast Milk Analysis: Role of Individualized Protein Fortification to Avoid Protein Deficit After Preterm Birth and Improve Infant Outcomes - Khaira, Sharmeel; Pert, Antoinette; Farrell, Emily; Sibley, Cecelia; Harvey-Wilkes, Karen; Nielsen, Heber C.; Volpe, MaryAnn V. (Frontiers in Pediatrics, 2022)
Background: Expressed breast milk (EBM) protein content is highly variable between mothers and often below published values that are still used for EBM protein fortification strategies. This approach may result in significant protein deficit and suboptimal protein energy (P/E) ratio. The study aim was to determine whether individualized EBM protein analysis and fortification will reduce preterm infant protein deficits and improve growth and neurodevelopmental outcome. Study Methods: In a single-center randomized, blinded study of infants born at 24 0/7 - 29 6/7 weeks, mother-specific protein values measured by a milk analyzer were used to individualize infant-specific protein intake (interventional group, IG), and compared this to a standardized protein fortification scheme based on published values of EBM protein content of 1.4g/dl (control group, CG). For IG, milk analyzer protein values of mother’s EBM was used to adjust protein content of the EBM. The CG EBM protein content was adjusted using the standard published value of 1.4 g/dl and not based on milk analyzer values. EBM protein content, protein intake, Protein/Energy (P/E) ratio, weight (WT), head circumference (HC), length (L) growth velocity (GV) from 2-6 weeks of age, WT, HC and L Z-Scores at 32 and 35 weeks PMA and lean body mass (35 weeks PMA skin fold thickness) were measured. Neurodevelopment was assessed by Bayley III at average 24 months corrected gestational age (CGA). Results: EBM protein content before fortification was significantly below published values of 1.4g/dl at all time points in both CG and IG. CG protein deficit was significantly decreased and progressively worsened throughout study. Individualized protein fortification in IG avoided protein deficit and optimized P/E ratio. Although no significant change in short-term GV (at 6 wks of age) was seen between groups, IG infants born at < 27 weeks had significant improvements in WT and L z-scores, and leaner body mass at 32 and 35 wks PMA. IG exhibited significantly improved cognitive scores at 24 months CGA. Conclusions: Infant-specific protein supplementation of mother’s EBM optimized P/E ratio by eliminating protein deficit and improved growth z scores at 32 and 35 weeks PMA and neurocognitive testing at 24 months.